FAKTOR PREDISPOSING YANG MELATARBELAKANGI PHBS KELUARGA BALITA PENDERITA ISPA - Inri Grizelda Laelaem; Dwi Helynarti Syurandhari; Asih Maedia Yuniarti (MEDICA MAJAPAHIT, 2023)
In Indonesia, infections of the respiratory tract can be caused by viruses and bacteria due to a lack of clean and healthy lifestyle (PHBS). The purpose of this study was to determine the relationship between predisposing factors and PHBS of families of toddlers with ISPA in the working area of the Gayaman Health Center in Mojokerto. Th is type of research is quantitative using the Cross 1Sectional method. The population was mothers of toddlers with ARI with a sample size of 80 respondents. The independent and related variables were examined at the same time as the research was being conducted, which aimed to determine the predisposing factors associated with PHBS of families of toddlers with ARI in the Gayaman Health Center Work Area. data were analyzed using the Chi Square Test. The results of data analysis showed that most of the respondents were aged 26-35 years, junior high school education, income did not meet the UMR, lack of knowledge and negative attitudes. Based on the Chi Square Test there is a relationship between Predisposing Factors and PHBS in families of toddlers with ISPA (ρ value ≤ 0.05). It is hoped that the results of this study can be used as material for recommendations in planning a PHBS improvement program as well as providing information to become material for additional insight for the community to pay more attention to environmental cleanliness in Families of Toddlers with ISPA in the Working Area of the Gayaman Health Center, Mojokerto Regency.